10.61533 PERAN SISTEM KEUANGAN DESA ONLINE (SISKEUDES) DALAM MENINGKATKAN KUALITAS AKUNTABILITAS KEUANGAN DESA DI DESA BENTENG KECAMATAN PANGKALAN BARU KABUPATEN BANGKA TENGAH - Saputra, Andre; Panjaitan, Fery; Medinal (STIE IBEK Pangkalpinang, 2024)
This research aims to find out how big the role of the Online Financial System (SISKEUDES) is in improving the quality of village financial accountability in Benteng Village, Pangkalan Baru District, Central Bangka Regency. The research method used in this research is qualitative with data collection techniques obtained from interviews and documentation. There were 4 informants in this research, namely the Village Head, Village Secretary, Finance Head and Planning Head. From the results obtained during the research, it can be concluded that the presence of SISKEUDES in Benteng Village helps the village accountability process to the local government and community with the village financial reports produced by this application. Then regarding the accountability of village financial reports, judging from the vertical and horizontal accountability indicators, the reporting and accountability of the Benteng Village Government has been said to be good or accountable. Benteng Village has implemented SISKEUDES which is adapted to Permendagri No. 20 of 2018 concerning Village Financial Accounting so that the quality of reporting can be accounted for based on applicable village accounting. Although there are still problems with the application which often causes errors.